Analisis program keluarga berencana menurut pandangan hukum islam - Lahitania, Zahra (Maliki Interdisciplinary Journal, 2025)
This study analyzes the Family Planning (FP) program within the context of Islamic law, focusing on scholars' perspectives regarding the application of contraceptive methods and devices within the program. The primary goal of the FP program is to manage births to improve the quality of life in society. However, there is a divergence of opinion among scholars regarding its legality in Islam. This research adopts a qualitative approach through literature review, involving an analysis of related literature and various scholarly fatwas. The findings indicate differing views within Islamic law on the FP program; some scholars permit its use under certain conditions, while others oppose it, especially concerning permanent contraceptive methods, which are seen as contrary to sharia principles. Considerations regarding health, welfare, and the purpose of FP use are crucial factors in determining its legality. This study is expected to provide a deeper understanding of the Islamic legal perspective on FP and serve as a reference for society and policymakers in formulating policies aligned with sharia principles.